Patients’ awareness towards the Value-added Services in Pharmacy Department, Hospital Tuanku Fauziah - Shamsuri, Nursyazwani; Alawi, Mohd Shahrul Azwan; Sham, Rasyiqah (2013)
The level of patients’ awareness towards the value-added services in Pharmacy Department, Hospital Tuanku Fauziah have been explored. Several types of Value- added Services available in Hospital Tuanku Fauziah, such as Integrated Drug Dispensing System or ‘Sistem Pendispensan Ubat-ubatan Bersepadu’ (SPUB), Medicine Services via Postal 1 Malaysia or ‘Ubat Melalui Pos 1 Malaysia ’ (UMP1M), Partial Drug Supply Immediately System or ‘BEkalan Segera ubat Separa ’ (BeSS), and Park and Take Immediately or ‘Letak Kereta Ambil Ubat Segera’ (LeKAS). The objectives of this study are to evaluate the level of awarenss of patients towards these services and to determine the level of interest of patients to use the value-added services. This study focuses on the number the patients who utilized, aware and interest towards the value-added services in Hospital Tuanku Fauziah,Kangar,Perlis. Our study subjects were patients with chronic diseases required long-term follow-up in Hospital Tuanku Fauziah. They were chosen randomly and were interviewed using a set of questionnaire (questionnaire-based interview). The focus in this study is to relate their demographic factors towards the level of awareness and the level of interest of patients towards the value-added services in Hospital Tuanku Fauziah. A total of 100 patients were recruited in the study. Our study shows that, 51 % participants were aware of these services. Instead, this research will be fully used soon to promote the value-added services in Pharmacy Department, Hospital Tuanku Fauziah. This will also provide information to pharmacy staffs in carrying out more effective programmes to promote value-added services among patients.